The balance of pro-inflammatory and anti-inflammatory cytokines in the fluid of the radicular cysts of the jaws in adults in asymptomatic and clinically manifest - I. S. Haidash; O. V. Burtsev (Patologìâ)
Aim. The aim of the work is to study the balance of pro-inflammatory and anti-inflammatory cytokines in the fluid of radicular jaw cysts in adults with asymptomatic and clinically manifest course of the disease.